2006
DOI: 10.1021/jf060145a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Inosine Monophosphate and Its Degradation Products during Aging of Pork of Different Qualities in Relation to Basic Taste and Retronasal Flavor Perception of the Meat

Abstract: Inosine monophosphate (IMP) and its degradation products, ribose and hypoxanthine, are all considered to be important constituents in meat flavor formation and development. The present study explored the fate of IMP during the aging of two qualities of pork (pH >5.7 and 5.5 < pH < 5.6) and the potential relationship between IMP, hypoxanthine, and sensory attributes of pork registered both as retronasal and basic taste responses in whole meat, meat juice, and the remaining meat residue. During aging the concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
87
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(100 citation statements)
references
References 20 publications
(25 reference statements)
4
87
0
3
Order By: Relevance
“…Earlier workers (Faustman and Cassens, 1991; Koutsidis et al, 2008a) studied on other cattle breeds also found that the Hx content was affected by the examined breed. IMP has been widely used as a flavor enhancer to increase palatability, its found to contribute to the sensory attributes like brothy and meaty (Chen et al, 2004;Tikk et al, 2006). The IMP contributes to the pleasant delicious taste and most to the umami taste by synergistic effect with MSG and GMP (Massa et al, 2003).…”
Section: Comparison Of Taste-active Compounds Between Hanwoo and Angumentioning
confidence: 99%
“…Earlier workers (Faustman and Cassens, 1991; Koutsidis et al, 2008a) studied on other cattle breeds also found that the Hx content was affected by the examined breed. IMP has been widely used as a flavor enhancer to increase palatability, its found to contribute to the sensory attributes like brothy and meaty (Chen et al, 2004;Tikk et al, 2006). The IMP contributes to the pleasant delicious taste and most to the umami taste by synergistic effect with MSG and GMP (Massa et al, 2003).…”
Section: Comparison Of Taste-active Compounds Between Hanwoo and Angumentioning
confidence: 99%
“…29,[43][44][45] Amino acids, peptides, nucleotides and sugars correspond to meat polar metabolites and, many of them are water-soluble precursors of meat flavour. [51][52][53][54] The presence of nucleotides in meat is important not only for the flavour but also because some nucleotides are considered biomarkers for relevant metabolic pathways. 52,55,56 For example, inosine monophosphate (IMP), inosine and hypoxantine are related to the purine degradation pathway which yields uric acid as end product.…”
Section: Redox Processes In Meatmentioning
confidence: 99%
“…[51][52][53][54] The presence of nucleotides in meat is important not only for the flavour but also because some nucleotides are considered biomarkers for relevant metabolic pathways. 52,55,56 For example, inosine monophosphate (IMP), inosine and hypoxantine are related to the purine degradation pathway which yields uric acid as end product. IMP is converted to inosine and inosine to hypoxantine during the post mortem metabolism of meat when degradation pathways take place.…”
Section: Redox Processes In Meatmentioning
confidence: 99%
See 2 more Smart Citations